2017
DOI: 10.1371/journal.pone.0177130
|View full text |Cite
|
Sign up to set email alerts
|

First report and molecular identification of Opisthorchis viverrini infection in human communities from Lower Myanmar

Abstract: Opisthorchis viverrini is endemic in the South East Asian region, especially in Cambodia, Lao People's Democratic Republic, Vietnam and Thailand, but there have been no previous records from Myanmar. During stool surveys of rural populations in three regions of Lower Myanmar, Opisthorchis-like eggs were found in 34 out of 364 (9.3%) participants by stool microscopy after using the modified formalin-ether concentration technique. DNA was extracted from these positive stool samples and a portion of the mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 27 publications
4
41
0
Order By: Relevance
“… 16 In Myanmar, O. viverrini infection was first reported in communities from lower Myanmar by Aung et al. 17 Their stool surveys of rural populations in three regions showed that the positive rate of Opisthorchis eggs was 9.30%. Our study is the second report of O. viverrini infection in humans from Myanmar, but is the first report on people from Myanmar who migrate to work in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“… 16 In Myanmar, O. viverrini infection was first reported in communities from lower Myanmar by Aung et al. 17 Their stool surveys of rural populations in three regions showed that the positive rate of Opisthorchis eggs was 9.30%. Our study is the second report of O. viverrini infection in humans from Myanmar, but is the first report on people from Myanmar who migrate to work in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…O. viverrini sensu lato is found in those countries bordering the Lower Mekong River in continental Southeast Asia. It appears to be most frequent in Lao PDR, the north and northeast of Thailand, parts of Cambodia, and southern Vietnam ( 9 ), with a recent first record from Myanmar ( 10 ). Evidence suggests that its range is restricted to areas occupied by its first intermediate hosts, freshwater Bithynia snails ( 11 ) (Figure 1 ).…”
Section: Current Situationmentioning
confidence: 99%
“…1 Opisthorchis viverrini infection is a major public health problem in the Southeast Asian region, especially in regions along the drainage of the lower Mekong River-Cambodia, Lao People's Democratic Republic, southern Vietnam, Myanmar, and Thailand, where people have cultures and dietary preferences for consumption of raw or undercooked freshwater fishes that are contaminated with encysted metacercariae of the liver fluke. 1,5,6 More than 10 million people are estimated to be infected with O. viverrini: about eight million people in Thailand and two million in Lao PDR, with approximately 67.3 million people, are at risk of the infection. 1 Clonorchis sinensis is the main helminth causing a major public health problem in Northeast and East Asia (northern Vietnam, China, and Korea).…”
Section: Introductionmentioning
confidence: 99%